Antimicrobial susceptibility and genetic characteristics of multi-drug resistant Acinetobacter baumannii isolates in Northwest China - Hu, Meimei; Sun, Hongjia; Xu, Yanmei; Xu, Xiaoying (Frontiers in Microbiology, 2024)
Introduction In recent decades, widespread multi-drug resistant (MDR) bacteria have become a serious problem in healthcare facilities. Methods To systematically summarize and investigate the prevalence and genomic features of clinical MDR Acinetobacter baumannii (A. baumannii) clinical isolates recovered from the first hospital of Lanzhou University, we collected 50 MDR A. baumannii isolates isolated in the first quarter of 2022 and using whole-genome sequencing investigate the genotypic characteristics. Results All of these isolates were generally resistant to the common β-lactamase antibiotics. Resistance to cefoperazone-sulbactam varies greatly between different clones. The proportion of CC208 isolates resistant and mediated to cefoperazone-sulbactam is as high as 84.6%. There were no isolates resistant to tigecycline and colistin. The presence of blaOXA − 23 (94.0%) and blaOXA − 66 (98.0%) were the most frequent determinants for carbapenem resistance. Two main endemic clones were identified, one (ST469oxf) was predominantly circulating in ICUs and carried the same resistance genes, virulence genes and transposons, and the other clone (CC208) carried more resistance genes and had more widely disseminated. Discussion Our study showed that clinical MDR A. baumannii isolates circulating in our hospital exhibited highly similar genetic features. We should take timely and effective measures to control the further epidemic of these isolates.